Efektivitas Pengawasan Majelis Pengawas Daerah (MPD) Kota Yogyakarta Terhadap Perilaku Notaris di Kota Yogyakarta menurut Kode Etik Notaris - NEKY KUNTJORO (Lex Renaissance, 2016)
AbstractProblems in the study: first, how the effectiveness of the supervision of the Regional Supervisory Council (MPD) Yogyakarta on behavior according Notary Notary Code? Second, whether the sanctions provided by the Regional Supervisory Council (MPD) of Yogyakarta to the Notary Public who Notary Code violations. To answer these problems juridical empirical research by reviewing the primary data and secondary data were analyzed descriptively. The study concluded, first, the implementation of supervision by the Supervisory Council of City of Yogyakarta have been effective because it is consistent with the supervision of working procedures of the Regional Supervisory Council. While Supervision and inspection of Notary conducted by the Supervisory Council, in which there are elements of Notaries , thereby at least Notary supervised and examined by the Supervisory Council members are definitely better understand the world Notary. Secondly, a notary who commit violations of the Code, the Honorary Board in coordination with the Council of Regional Supervisor will check such violations, and may impose sanctions on violators, sanctions imposed upon members of the Indonesian Notary Association who violates the Code of Conduct, according to Article 6 of the Notary Code, namely form: 1. Reprimand; 2. Warning; 3. Schorzing (temporary dismissal) of the membership associations; 4. Onzetting (dismissal) of the membership associations; 5. Dismissal with no respect from the membership association.Keywords: Development and Supervision